PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN MEDIA POP UP BOOK DILENGKAPI LKS LIVEWORKSHEET UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IX DI SMP MUHAMMADIYAH WAINGAPU - Kalita Mboru, Asrince; Makaborang, Yohana; Ndjoeroemana, Yohana (Universitas Cokroaminoto Palopo, 2024)
This study aims to provide a comprehensive overview of how the Think Pair share learning model is assisted by pop-up book equipped With Stundet liveworksheets, as well as to describe the improvement in students' learning outcomes after applying this model and instructional media. Conducted as a Classroom Action Research (CAR), the study utilizes a descriptive quantitative approach. The subjects of this research are students of IX class at Smp Muhammadiyah Waingapu, State Junior High School. Data collection instruments include observation sheets and written tests. The research findings indicate a significant increase in cognitive learning outcomes, from 27% in the pre-cycle to 56% in cycle I, and further increasing to 93% in cycle II. Additionally, affective learning outcomes also experienced improvement, from 30% in the pre-cycle to 53% in cycle I, and reaching 93% in cycle II. Therfore it can be concluded that implementing the Think Pair share learning learning model assistd Pop-up book media equipped with liveworksheets lks can inmprove outcomes.